Contracting without contracting institutions: The trusted assistant loan in 19th century China - Miao, Meng; Niu, Guanjie; Noe, Thomas (Journal of Financial Economics, 2021)
This paper documents the emergence of a large bank loan market in the absence of contracting institutions: the trusted assistant loan market in 19th century China. These loans were legally unenforceable, one-shot loans to poor scholars that funded the costs of assuming lucrative administrative appointments offering ample opportunities for corruption. The trusted assistant loan’s distinguishing feature was a legally unenforceable stipulation that the borrower incorporate an agent of the creditor into his administrative cadre. We model the enforcement of these loans through expertise leverage and test the model’s predictions using data from officials’ diaries and a bank loan book.